Pembuatan Animasi 2D "Nampak Gonggong" sebagai Media Pengenalan Batik Gonggong - Janah, Nurul; Lumombo, Laura; Cahyono, Yusuf Rizky Nur (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
This research aims to introduce and preserve gonggong batik as one of the local cultural heritages of the Riau Islands through 2D animation media. The problem raised is the declining interest of the younger generation in gonggong batik, which is caused by a lack of promotion and understanding of its cultural value. This research uses a creative method, starting from visual observation of gonggong batik motifs and collecting related literature data. The production process includes pre-production stages (idea formulation, script writing, storyboarding, character design, and batik design), production (visual asset creation, rigging, animation with cut-out animation techniques, and adding visual effects), to post-production (compositing, editing, color correction, and adding audio). The final result is a 1 minute 14 second animated trailer video in Full HD resolution published on YouTube. Through 2D animation media that combines visual power and storytelling, this work is expected to be an interesting educational tool and support efforts to preserve gonggong batik, as well as contribute to the development of local cultural promotional media.